The Prevalence of Transactional Sex and its Implications for Female Trade Apprentices in the Bono Region-A Case Study of the Sunyani Metropolis. - Sagoe, Prince George (UniMAC-GIJ, 2021)
This study focused on the prevalence of Transactional Sex and its implications for Female Trade Apprentices using the Sunyani Metropolis in the Bono Region as a case study. Transactional sex, is not the same as Prostitution. In prostitution, the client pays as he calls , and there is rarely any romantic entanglements. In Transactional sex however, the female provides sex to the male in exchange for gifts and financial inducements, nonetheless, it is the female’s prerogative (agency) to accept the proposal of the male or not, and the relationship is long-lasting, and has a romantic inflection. The literature claims that females engaged in transactional sex, often have no power, or control of the relationship, and are abused in what is described as intimate partner violence. They are also noted to often have more than one male friend at a time, who invariably may be from five or more years older than the female (Intergenerational sex). However, the point of departure of this study, is that the females exercise some appreciable level of control and power over the relationship, they are not beaten nor excessively controlled by their male partners, and rarely date more than one man at a time. This is a departure from the usual claims one finds in the literature. Accordingly, ,this study investigates the differences in the practice of Transactional Sex and its implications for Female Trade Apprentices in the Sunyani Metropolis in the Bono Region. This study employed peer reviewed articles, newspaper reports, internet news portals, websites and a quantitative approach based on a survey questionnaire. Findings and information from existing literature do not only affirm that transactional sex is prevalent in the metropolis but also, has a pernicious effect on females - For instance, many ladies get used to the fact that several men contribute to their upkeep, so when they marry, they find it difficult to be content with the support of one man. This leads to the breakdown of many relationships. One lady said she took on a second boyfriend because she and her permanent boyfriend were facing financial challenges. This indicates that she is in a relationship with more than one man, at the same time, which could expose her to sexually transmitted infections including HIV and AIDS, a major claim in most literature. In conclusion, though a few of such cases occur, they are not indicative of the general. It is recommended that further qualitative study be done to dig deeper into causes and drivers of transactional sex.
Thesis
Keywords: Transactional Sex, Female Trade Apprentices, Bono Region, Sunyani Metropolis.